Studi Pengelolaan Sampah Pasar Panakkukang Kota Makassar: Kecamatan Panakkukang Kota Makassar - Pasoa, Muh. Rusmanwadi R.; Abduh, M. Natsir; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The market is a public facility that functions as a place to channel community needs in the context of economic activities. The market as a place where buying and selling takes place between sellers and buyers is one of the largest sources of waste in Indonesia, where 22.78% of the 22.36 million tons of waste comes from the market in 2022. This research aims to find out the existing waste management system, volume waste generation and knowing the effective and efficient waste management system at Panakkukang Market, Makassar City. This research uses a quantitative approach, with a total of 23 waste generation measurement points from 9 types of samples. The results of this research are that waste management at Panakkukang Market is carried out using individual storage, direct individual collection, and waste transportation using a compactor truck with a capacity of 9000 Lt. Apart from that, the amount of waste generated by Panakkukang Market is 6,092 liters/day, and to make the waste management process more effective and efficient, it can be done by paying attention to the storage, collection and transportation of waste in accordance with SNI-2454-2002 and maximizing the participation of the community to participate in optimizing waste management such as composting, recycling or reusing waste (3R).